2011
DOI: 10.1007/s13402-011-0019-7
|View full text |Cite
|
Sign up to set email alerts
|

Phospho-proteomic analysis of mantle cell lymphoma cells suggests a pro-survival role of B-cell receptor signaling

Abstract: BackgroundMantle cell lymphoma (MCL) is currently an incurable entity, and new therapeutic approaches are needed. We have applied a high-throughput phospho-proteomic technique to MCL cell lines to identify activated pathways and we have then validated our data in both cell lines and tumor tissues.MethodsPhosphoScan analysis was performed on MCL cell lines. Results were validated by flow cytometry and western blotting. Functional validation was performed by blocking the most active pathway in MCL cell lines.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 56 publications
2
62
0
Order By: Relevance
“…A recent proteomic screen of phosphorylated proteins in MCL cells indicated that proteins connecting the B-cell receptor (BCR) signaling network were among the most abundant proteins found, and active BCR signaling in MCL cells was confirmed by flow cytometry (66). As depicted in Fig.…”
Section: B-cell Receptor Signaling Pathway: Targeting Bruton Tyrosinementioning
confidence: 90%
“…A recent proteomic screen of phosphorylated proteins in MCL cells indicated that proteins connecting the B-cell receptor (BCR) signaling network were among the most abundant proteins found, and active BCR signaling in MCL cells was confirmed by flow cytometry (66). As depicted in Fig.…”
Section: B-cell Receptor Signaling Pathway: Targeting Bruton Tyrosinementioning
confidence: 90%
“…Amplification and overexpression of the spleen tyrosine kinase (SYK) and the PI3K catalytic α polypeptide have been found in a subset of MCL (40,41). Furthermore, different kinases of the BCR signaling, including SYK, LYN, and BTK, have been found to be phosphorylated in primary MCL, suggesting activation of the pathway (42).…”
Section: Signaling Pathways Deregulated In MCLmentioning
confidence: 99%
“…Once phosphorylated, Lyn and Syk propagate the BCR signal by activating downstream kinases, such as Btk, resulting in the activation of multiple downstream signaling pathways. Recently, it has been reported that MCL cells have constitutive activation of the BCR signal transduction proteins Syk and PKCbII (6,7), as well as high expression of the phosphorylated forms of these and other BCR-associated kinases (8).…”
Section: Introductionmentioning
confidence: 99%